1994
DOI: 10.1073/pnas.91.10.4427
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of ischemia-induced ventricular fibrillation by omega 3 fatty acids.

Abstract: A specially prepared dog model of myocardial infarction was used to test the efficacy of the long-chain polyunsaturated fish oil 3 fatty acids eicosapentaenoic (20:5 n-3) and docosahexaenoic (22:6 n-3) acids to prevent ischemiainduced malignant cardiac arrhythmias. The dogs had sustained a prior experimental myocardial infarction from ligation of the left anterior descending coronary artery, and a hydraulic cuff was implanted around the left circumflex artery at that operation. After recovery from that procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
138
3
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(156 citation statements)
references
References 18 publications
12
138
3
3
Order By: Relevance
“…The strength of the effect of the fatty acids on voltage dependence increases with the number of C=C unsaturated bonds. Since esterified PUFAs were without effect in vitro (9) and in vivo (15), the apparent structural requirements for affecting INa have been proposed to be a long hydrocarbon chain with two or more unsaturated C=C bonds and a free carboxylic acid group at one end (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the effect of the fatty acids on voltage dependence increases with the number of C=C unsaturated bonds. Since esterified PUFAs were without effect in vitro (9) and in vivo (15), the apparent structural requirements for affecting INa have been proposed to be a long hydrocarbon chain with two or more unsaturated C=C bonds and a free carboxylic acid group at one end (23).…”
Section: Resultsmentioning
confidence: 99%
“…Diets enriched with fish oils or n-3 fatty acids prevented fatal ventricular arrhythmias in rats (10,11) and probably in humans (12)(13)(14). Furthermore, infusion of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) intravenously just before an ischemic event prevented ventricular fibrillation in exercising dogs (15).…”
Section: Introductionmentioning
confidence: 99%
“…protective antiarrhythmic effect of ingestion of fish or fish oil has been shown to be attributable to their eicosapentaenoic acid (EPA; C20:5 n Ϫ 3) and docosahexaenoic acid (C22:6 n Ϫ 3) content as demonstrated by administering a highly concentrated fish oil preparation of free n Ϫ 3 PUFAs intravenously just before the ischemic challenge and preventing the fatal arrhythmias (4). But studies with isolated cultured neonatal rat cardiac myocytes showed that polyunsaturated fatty acids, both n Ϫ 6 and n Ϫ 3, are antiarrhythmic during Ca 2ϩ overload (8).…”
mentioning
confidence: 99%
“…Certainly, long-term statin treatment by modulating the lipid portions of the sarcolemma, which contain the ion channel regulatory proteins and signalling molecules (lipid rafts), influence the ion channel conduction and ion transport (Maguy et al, 2006;Vyas et al, 2006), but it is not known whether such a mechanism would also account for the acute administration of statins. Nevertheless, considering that polyunsaturated fatty acids, which alter the structure of the sarcolemmal phospholipids, were able to evoke immediate antiarrhythmic effect (Billman et al, 1994;Kang and Leaf, 2000;Leaf et al, 2003), we may speculate that statins perhaps also possess such acute modulator properties on the lipid portions of the membrane. This, by causing favourable changes in ion transport or by stabilizing the membrane, would lead to arrhythmia suppression during ischaemia.…”
Section: Discussionmentioning
confidence: 99%